SINERGITAS KEBIJAKAN LEMBAGA ADAT PETANI DALAM PENANGGULANGAN KEMISKINAN DI KABUPATEN ACEH BARAT - Mardhiah, Nellis; Syahputri, Veni Nella; Nodi Marefanda, Nodi Marefanda; Macella, Agatha Debby Reiza (JURNAL TRIAS POLITIKA, 2024)
Abstract: The aim of this research is to understand the synergy pattern implementation of government policies in accordance with the qanun of traditional farmer institutions number 10 of 2008 in article 25 discusses about traditional farmer institutions have duties and functions that can be synergized by the government village. The rice farming community is always on the poverty line, the dynamics of the socio-economic layers of the farming community are still very attached to values and culture which are often ignored by the government and traditional institutions with unidirectional organizational communication patterns, there are conflicts of interest in increasing the productivity of rice agricultural products. The SDGs-18 Development Target for farming communities is an element of strengthening dynamic village institutions and an adaptive culture which is one of the development prospects in changing the direction of social policy and community empowerment for village development in overcoming poverty. The traditional institution "Keujreng Blang" is one of the roles and functions of rice farming governance which has the potential to create food security which can be integrated through village SDGs development based on farmers' traditional villages. This research method was implemented using a qualitative approach in the form of a phenomenological approach to the socio-economic conditions of society in a more in-depth and comprehensive way towards the problems being analyzed. The research results policy synergy show that rice farming governance cannot be properly integrated by regional governments because the dynamics of policy and the position of traditional institutions at the village level are still assumed by the government. Therefore, it is expected that the government can formulate inclusive policies for traditional institutions in improving agricultural governance in a sustainable way to overcome community poverty. Abstrak: Tujuan Penelitian ini ingin mengetahui pola sinergitas pelaksanaan kebijakan pemerintah sesuai dengan qanun lembaga adat petani nomor 10 Tahun 2008 dalam pasal 25 yakni lembaga adat petani adanya tugas dan fungsi yang dapat disinergikan oleh pemerintah desa. Masyarakat petani padi senantiasa berada digaris kemiskinan, dinamika lapisan sosial ekonomi masyarakat petani masih sangat melekat dengan nilai dan budaya sering diabaikan oleh pemerintah dan lembaga adat dengan pola komunikasi organisasi yang tidak searah, terjadi konflik interest dalam peningkatan produktivitas hasil pertanian padi. Sasaran Pembangunan SDGs-18 bagi masyarakat petani merupakan unsur penguatan kelembagaan desa yang dinamis dan budaya adaptif yang salah satu prospek pembangunan dalam mengubah arah kebijakan sosial dan pemberdayaan masyarakat untuk pembangunan desa dalam penanggulangan kemiskinan. Lembaga adat “Keujruen Blang” adalah salah satu peran dan fungsi tata kelola pertanian padi yang berpotensi menciptakan ketahanan pangan yang dapat diintegrasikan melalui pembangunan SDGs desa yang berbasis desa adat petani. Metode penelitian ini dilaksanakan pendekatan kualitatif dengan bentuk pendekatan fenomenalogis keadaan sosial ekonomi masyarakat secara lebih mendalam dan komprehensif terhadap permasalahan yang dianalisis. Hasil Penelitian menunjukkan sinergitas kebijakan dalam tata kelola pertanian padi belum dapat diintegrasikan dengan baik oleh pemerintah daerah dikarenakan dinamika kebijakan dan kedudukan kelembagaan adat diperingkat desa masih semu di asumsikan oleh pemerintah. Maka dengan demikian diharapkan kepada pemerintah dapat memformulasikan kebijakan inklusif bagi lembaga adat agar peningkatan tata kelola pertanian dengan baik dalam penanggulangan kemiskinan masyarakat secara berkelanjutan.